2018
DOI: 10.1001/jamadermatol.2018.0364
|View full text |Cite
|
Sign up to set email alerts
|

The Vedic View of Vitiligo

Abstract: Dermatology Forum (EDF); European Association of Dermato-Oncology (EADO); European Organization for Research and Treatment of Cancer (EORTC). Diagnosis and treatment of invasive squamous cell carcinoma of the skin: European consensus-based interdisciplinary guideline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 2 publications
(9 reference statements)
1
10
0
Order By: Relevance
“…There are several implications from the study by Patel et al for a patient with a diagnosis of melanoma in situ; one of these is a heightened risk of developing a subsequent primary melanoma and thus a need for ongoing routine skin checks. Using the SEER data, Patel et al found that after a diagnosis of melanoma in situ, the 15-year cumulative incidence was 8.9% for a second primary invasive melanoma and 14.1% for a second primary melanoma in situ. This is consistent with other studies .…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…There are several implications from the study by Patel et al for a patient with a diagnosis of melanoma in situ; one of these is a heightened risk of developing a subsequent primary melanoma and thus a need for ongoing routine skin checks. Using the SEER data, Patel et al found that after a diagnosis of melanoma in situ, the 15-year cumulative incidence was 8.9% for a second primary invasive melanoma and 14.1% for a second primary melanoma in situ. This is consistent with other studies .…”
mentioning
confidence: 99%
“…In this issue of JAMA Dermatology , Patel and colleagues examine mortality after a diagnosis of melanoma in situ. Melanoma in situ is the earliest stage of melanoma (stage 0) and is localized to the outermost layer of skin (epidermis).…”
mentioning
confidence: 99%
See 3 more Smart Citations